Predicting compression failure of composite laminates in fire - Summers, P.T.; Lattimer, B.Y.; Case, S.; Feih, S. (Composites. Part A, Applied science and manufacturing, 2012)
A thermo-structural model was developed and validated to predict the failure of compressively loaded fiber-reinforced polymer (FRP) laminates during one-sided heating from a fire. The model consists of a one-dimensional pyrolysis model to predict the thermal response of a decomposing material and an integral structural model based on the bending equation. The thermo-structural model predicts temperatures, out-of-plane deflections, and compressive failure of laminates exposed to fire conditions. Model results were validated with intermediate-scale compression load failure tests with a one-sided heat flux exposure. Through a sensitivity analysis of the model predictions to input parameters, the residual elastic modulus was determined to be of utmost importance to both prediction of out-of-plane deflection and time-to-failure.